Use of timber panels to reduce the seismic vulnerability of concrete frame structures. (1st October 2021) - Smiroldo, Francesco; Giongo, Ivan; Piazza, Maurizio
Highlights: A new method that uses timber panels to retrofit seismically-vulnerable reinforce concrete structures is proposed. Over 200 reinforced concrete frames retrofitted with CLT panes are studied via finite-element modelling. The efficacy of timber-based strengthening of reinforced concrete frames is evaluated on four-storey building. Abstract: This paper discusses a seismic retrofit method that is intended for reinforced concrete (RC) frame structures and that sees the replacement of the existing masonry infills with timber structural panels. The intervention is aimed at enhancing the overall behaviour of the buildings without modifying the original concrete structural system. In the presented research over 200 finite-element models comprising bare, masonry-infilled and retrofitted single-storey single-bay frames were subjected to nonlinear static analyses. The response of the timber-infilled frames was then optimised, thus enabling the definition of a few simple design rules to guide the implementation of the retrofit system. Subsequently, the efficacy of the proposed solution was further investigated by applying the timber-based retrofit to an entire case-study building modelled via finite elements and subjected to nonlinear static pushover analysis. The comparison of the results obtained for the building in the original and retrofitted configurations indicates that the proposed system can favour the development of ductile behaviours and improve the seismic response of RC frame structures significantly.